2008
DOI: 10.1111/j.1540-8183.2007.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Characteristics of Culprit Sites in Acute Coronary Syndromes

Abstract: Specific anatomic features of the coronary arteries predispose to development and/or subsequent rupture of vulnerable plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…In accordance with previous angiographic [16,17], intravascular ultrasound [18,19], CT, [20] and pathology [2] studies, we identified the proximal LAD as the site of both plaque formation and rupture. Our data indicate that plaque rupture and subsequent thrombosis in particular, seem to occur most often in the segment between 2 and 4 cm from the origin of the LAD.…”
Section: Discussionsupporting
confidence: 85%
“…In accordance with previous angiographic [16,17], intravascular ultrasound [18,19], CT, [20] and pathology [2] studies, we identified the proximal LAD as the site of both plaque formation and rupture. Our data indicate that plaque rupture and subsequent thrombosis in particular, seem to occur most often in the segment between 2 and 4 cm from the origin of the LAD.…”
Section: Discussionsupporting
confidence: 85%
“…However, that study, which used 2-dimensional angiographic imaging, was limited to a qualitative analysis, and the torsion motion was not clarified. The proximal LAD artery is the most frequent site of plaque rupture resulting in acute coronary syndrome [18][19][20][21]. The cyclic longitudinal compression and torsion that we observed at the proximal LAD artery might represent mechanical causes of plaque rupture and in-segment restenosis after coronary stent implantation.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, sLOX levels were shown to be associated with coronary lesion sites: patients with lesions at the proximal or middle segments of the left anterior descending artery (LAD) had higher sLOX-1 levels than did those with lesions at the distal segment of the LAD [71]. These anatomical differences in sLOX levels may also be explained by CAD severity, because proximity is known to reflect the rupture risk of vulnerable plaques and thus the subsequent development of thrombotic lesions [72]. In a prospective study with a median follow-up period of 896 days in ACS patients undergoing emergency percutaneous coronary intervention, serum sLOX-1 levels were higher in patients who died or who experienced ACS recurrence, indicating that sLOX may predict the prognosis of ACS [73].…”
Section: Lox-1 In Patients With Cadmentioning
confidence: 94%